Work experience of breastfeeding nurses returning to work after maternity leave in Liaoning Province of China: A qualitative study - Xin‐li Wan; Jia‐yi Yang; Ying‐li Pan (Wiley, 2024)
Abstract Aim With the implementation of China's three‐child policy in 2021, the nurse population faces an increase in the number of breastfeeding nurses returning to work after maternity leave. This study aims to describe the work experience of breastfeeding nurses returning to work after maternity leave. Design A qualitative descriptive design. Methods The data were collected through semi‐structured interviews with eight nurses and analysed through Braun and Clarke's thematic analysis. Results Three themes and nine sub‐themes emerged from the analysis of the interviews: changes in nurses (emotional changes, physical changes and changes in work); needs for an improving work environment (needs for a supportive workplace and nurse shortage); support for breastfeeding nurses (support from coworkers, support from the manager, support from the organisation and own need for work). Public Contribution This study highlighted that breastfeeding nurses need an adjustment period when they return to work after maternity leave. Successful breastfeeding requires support from coworkers, managers and the organisation. In addition, workplace support for breastfeeding and management for nurses needs to be improved.